Islamic doctrine on mass media: from theological assumptions to the practical ethics of the media - Piwko, Aldona (Journal for the study of religions and ideologies, 2021)
The article is to present, discuss and juxtapose the official doctrine of Islam on the subject of social media (mass media). The authors want to answer the following questions: How is the official religious doctrine formed in Islam, and who influences its creation? What is the issue of religious authority in Islam? Does the official religious doctrine of Islam refer directly to the mass media, and if so, how and what practical implications do this result from? Finally - last but not least - to what extent can we speak of Islamic media ethics? According to the authors, the role of the media in the Muslim world is currently strongly dependent on the political, social, economic and cultural context of a given country. The Qu’ran has paramount importance for the theology of media in the Muslim world but understood primarily as an exponent of acting in accordance with God's commands and an indicator of morality in the world of Islam. The implementation of Quranic principles in modern times is subject to the risk of misinterpretation made by man. That is why not every part of the Muslim world accepts theological novelties. Probably, for this reason, ethics remains an extremely important element of Muslim media theology.